Interdisciplinary management for chronic pain in central neurological disorders: a retrospective study. (2nd January 2020) - Young, Jamie; Mantopoulos, Steven; Blanchard, Megan; Tardif, Hilarie; Hogg, Malcolm; Khan, Fary; Galea, Mary P
Abstract : Background/aims: Chronic pain in central neurological disorders is common and the current management of chronic pain is through an interdisciplinary approach. The aim of this study was to compare outpatient interdisciplinary-based treatment for chronic pain in patients with central neurological disorders to those without central neurological disorders. Methods: This was a retrospective study and pain-related outcome measures were collected from a clinical outcomes registry (electronic Persistent Pain Outcomes Collaboration). This registry contained data on people who attended a pain management service who, for the purpose of this study, were categorised into those with a central neurological disorder and those without a central neurological disorder. The two sample t -test was used to determine the significance of the difference between the groups and statistical significance was defined as P <0.05. Outcome measures compared included the Brief Pain Inventory, Depression, Anxiety and Stress Scale 21, Patient Self-efficacy Questionnaire and Patient Catastrophisation Scale. Results: There was a total of 1924 participants with a central neurological disorder. The electronic Persistent Pain Outcomes Collaboration registry shows that after engagement with an interdisciplinary pain management service, there was a reduction in pain severity scores, interference, mean depression, anxiety and stress in both groups at end of an episode of care compared to referral. There was a significant difference in mean changes for pain catastrophising between those with a central neurological disorder (−10.3) and those without (−7.8). Conclusions: This study shows that people with central neurological disorders can also benefit from interdisciplinary management and have similar results to those without these conditions.